Solving the Hotdog Problem by Using the Joint Zero-order Finite Hankel - Elzaki Transform (Baghdad Science Journal, 2023)
This paper is concerned with combining two different transforms to present a new joint transform FHET and its inverse transform IFHET. Also, the most important property of FHET was concluded and proved, which is called the finite Hankel – Elzaki transforms of the Bessel differential operator property, this property was discussed for two different boundary conditions, Dirichlet and Robin. Where the importance of this property is shown by solving axisymmetric partial differential equations and transitioning to an algebraic equation directly. Also, the joint Finite Hankel-Elzaki transform method was applied in solving a mathematical-physical problem, which is the Hotdog Problem. A steady state which does not depend on time was discussed for each obtained general solution, i.e. in the boiling and cooling states. To clarify the idea of temperature rise and fall over the time domain given in the problem, some figures were drawn manually using Microsoft PowerPoint. The obtained results confirm that the proposed transform technique is efficient, accurate, and fast in solving axisymmetric partial differential equations.